Remote warfare as "security of being": reading security force assistance as an ontological security routine. Issue 4 (2nd October 2021) - Riemann, Malte; Rossi, Norma
ABSTRACT: This article analyses remote warfare from an ontological security perspective, arguing that remote warfare needs to be understood as a response to states' internal self-identity needs. We develop this claim by analysing an emerging aspect of remote warfare: Security Force Assistance (SFA). SFA is aimed at building up the security forces of partners, sharing best practice, assisting in security sector reform, fostering collaboration, and overall contributing to conflict resolution. Focusing on the UK, we show how and why ontological security needs are a driving force behind the UK's SFA program. We outline the UK's specific autobiographical narrative, which we call a "global engagement identity, " explore the crises that induced ontological insecurity, and show how the UK's SFA program can be read as a routinised foreign policy practice aimed at taming uncertainty and reinforcing ontological security. This paper makes three contributions. First, it analyses remote warfare through an ontological security framework, thereby moving the focus from "security-as-survival" to "security-of-being." Second, it highlights the importance of SFA as a remote warfare tool. Third, it shows the centrality of ontological security in understanding UK defence policy.